2022
DOI: 10.3390/agriculture12050581
|View full text |Cite
|
Sign up to set email alerts
|

Motion Planning of the Citrus-Picking Manipulator Based on the TO-RRT Algorithm

Abstract: The working environment of a picking robot is complex, and the motion-planning algorithm of the picking manipulator will directly affect the obstacle avoidance effect and picking efficiency of the manipulator. In this study, a time-optimal rapidly-exploring random tree (TO-RRT) algorithm is proposed. First, this algorithm controls the target offset probability of the random tree through the potential field and introduces a node-first search strategy to make the random tree quickly escape from the repulsive pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…To further verify the effectiveness of the gripper harvesting, the tests for the three cases of rigid fingers and soft fingers with or without slip detection under the gripper structure of this study were carried out, as shown in When the slip detection is turned off, we define the visible slippage as the fruit that is about to slide to the fingertips of the gripper or that has already broken from the gripper (the same as below). 2 Because the fruit damage due to slippage in the gripper and due to grasping are quite different in character, we can distinguish them more easily (the same as below). 1 With slip detection on, the second slippage of the fruit means that the picking has failed.…”
Section: Of 26mentioning
confidence: 99%
See 1 more Smart Citation
“…To further verify the effectiveness of the gripper harvesting, the tests for the three cases of rigid fingers and soft fingers with or without slip detection under the gripper structure of this study were carried out, as shown in When the slip detection is turned off, we define the visible slippage as the fruit that is about to slide to the fingertips of the gripper or that has already broken from the gripper (the same as below). 2 Because the fruit damage due to slippage in the gripper and due to grasping are quite different in character, we can distinguish them more easily (the same as below). 1 With slip detection on, the second slippage of the fruit means that the picking has failed.…”
Section: Of 26mentioning
confidence: 99%
“…The high labor cost in the harvesting stage limits the fruit industry's development. With this backdrop, fruit-picking robots have become a hotspot for study in related fields [1,2]. Researchers have completed several projects and made significant progress in important technologies such as robot perception and positioning [3,4], system integration [5], and efficient harvesting end effector design.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-heuristic algorithms include the ant colony algorithm [ 4 ], particle swarm algorithm [ 5 ], and gray wolf algorithm [ 6 ]. From the aspect of traditional algorithms, Liu et al [ 7 ] proposed a time-optimal rapidly-exploring random tree (TO-RRT) algorithm for the path planning of citrus picking robots. The method controls the target offset probability of the random tree through the potential field.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, citrus color approximation and prediction are based on the experience of investigators, which lacks accuracy and is constrained to those with such capability. Advances in machine vision techniques have attracted a lot of attention because of their nondestructive and objective nature, and they have been successfully deployed for a variety of precision agriculture tasks including the characterization of plant varieties [ 7 11 ], robotic harvesting [ 12 , 13 ], and diseases diagnosis [ 14 , 15 ]. Jiménez-Cuesta et al.…”
Section: Introductionmentioning
confidence: 99%